2011
DOI: 10.1111/j.1463-5224.2011.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Feline glaucoma—a comprehensive review

Abstract: Cats with glaucoma typically present late in the course of disease. It is likely that glaucoma in cats is under-diagnosed due to its insidious onset and gradual progression, as well as limitations of some commonly used tonometers in this species. Treatment of glaucoma in feline patients presents a clinical challenge, particularly as glaucoma is often secondary to other disease processes in cats. In this review, we consider the clinical features, patho-physiology and classification of the feline glaucomas and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 65 publications
2
80
0
Order By: Relevance
“…IOP values above the normal range are indicative of glaucoma, and values below the normal range are indicative of uveitis (COLITZ, 2005;MILLER, 2011;SHUKLA;PINARD, 2012;STILES, 2013), which agrees with the observations of this study. In the ambulatory study, the mean IOP value measured with the Kowa HA-2 tonometer for the eyes with clinical signs of glaucoma was 38.4 ± 8.1 mmHg (29.6 -53.7), which was above the measured value in the healthy eyes (15.0 ± 1.5 mmHg).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…IOP values above the normal range are indicative of glaucoma, and values below the normal range are indicative of uveitis (COLITZ, 2005;MILLER, 2011;SHUKLA;PINARD, 2012;STILES, 2013), which agrees with the observations of this study. In the ambulatory study, the mean IOP value measured with the Kowa HA-2 tonometer for the eyes with clinical signs of glaucoma was 38.4 ± 8.1 mmHg (29.6 -53.7), which was above the measured value in the healthy eyes (15.0 ± 1.5 mmHg).…”
Section: Discussionsupporting
confidence: 82%
“…The pathophysiological process of glaucomatous optic neuropathy is likely to be a multifactorial event. An increase in IOP is the principal risk factor for glaucoma, and the primary goal of treatment is to reduce IOP to a value that prevents the death of retinal ganglion cells (XU et al, 2014;STRUEBING;GEISERT, 2015;TEIXEIRA et al, 2014;MILLER, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, this should not be translated to medical treatment of glaucoma in small animals. In view of the previously cited results of , the side effects in general preclude the use of apraclonidine in cats (McLellan and Miller 2011). Considering the results of a retrospective study reported by the ASPCA Animal Poison Control Center (Welch and Richardson 2002), the administration safety of 0.2% brimonidine in dogs also raises doubts.…”
Section: Clinical Usementioning
confidence: 92%
“…No significant additive ocular effect was detected in normotensive cats treated with a combination of dorzolamide (2%) and timolol (0.5%) relative to the IOP-lowering effect of treatment with dorzolamide alone (Dietrich et al 2007). These data indicate that a CAI alone can maximally suppress AH formation in cats (McLellan and Miller 2011). As β 2 -adrenergic receptors predominate in the feline anterior segment (Colasanti and Trotter 1981), β 1 -selective blockers, i.e.…”
Section: Effect On Iopmentioning
confidence: 98%
See 1 more Smart Citation